Paolo Portoghesi con Vittorio Gigliotti, Mezquita y Centro Cultural Islámico de Roma, 1974-1995 - Giulio Saponaro; Gentucca Canella; Tanja Marzi; Lorenzo Savio; Maurizio Villata; Frank Alexander Ramirez Gaitan (Bienal Panamericana de Arquitectura de Quito, Colegios de Arquitectos del Ecuador Provincia de Pichincha, 2024)
The essay intends to analyse the complex of the Great Mosque with the Islamic Cultural Centre built in Rome by Paolo Portoghesi, with Vittorio Gigliotti and Sami Mousawi. It retraces the controversial public debate that marked the main place of worship of the Muslim community in Italy, from the international competition phases of 1973, to those of the project and then of the construction site, until 1995, the year of completion of the works and inauguration. In fact, some initial positions taken by the Roman community and some criticism on the choice of the location can be considered partially justified - an area on the hill previously designated by the Town Plan as a public green area, too "constrained" by the existing infrastructures and, moreover, not responsive to the initial intentions of the designers. On the contrary, the subsequent resistance to the innovative figurative, typological and formal solutions adopted by the authors in combining the lexicon and types of the Islamic tradition with the genius loci of Rome appear completely unfounded, even in the strictly political attempt and of civil commitment, of an essential religious and cultural integration. «It is therefore [for Portoghesi] an experimentalism of reason and dreams, however secular [.] Experimentalism which, however, tested in the monument of the Mosque of Rome, has shown to be able to sublimate itself by purifying itself in that interweaving-synthesis between two parallel civilizations of architecture, of the East and the West, which I personally consider being one of the few memorable works of our years" (Guido Canella, 1993, p.21).